An Analysis of Economic Challenges of Fuel Cell Commercialization (International Journal of Innovative Research in Computer Science & Technology, 2020)
Financial development should depend on  more harmless to the ecosystem and proficient creation  processes as asset shortage, outrageous environmental  change, and contamination levels rise. As a result of their  high effectiveness and harmless to the ecosystem activity,  energy components are an optimal option in contrast to  interior ignition (IC) motors and boilers on the way to  greener enterprises. Be that as it may, as another energy  innovation, power devices presently can't seem to  accomplish critical market infiltration. We use life cycle  and worth chain exercises to direct a techno-financial and  ecological investigation of energy component frameworks  in this examination. In the first place, we investigate the  course of energy component improvement and figure out  which exercises ought to be completed in light of the power  module life cycle, esteem chain, and end-client  acknowledgment standards. Following that, we present a  solidified comprehension of the institutional obstructions  to energy component commercialization. To acquire an  upper hand, an energy component should outflank its  rivals, like IC motors and batteries, on the essential end client acknowledgment standards of capacity, cost, and  unwavering quality. Energy component fix and support  costs (because of their low unwavering quality) can bring  about tremendous expense increments and diminished  accessibility, the two of which are significant variables in  end-client acknowledgment. The energy component  industry should sort out some way to get through this  unwavering quality obstruction. This paper dives further  into our work on the fundamental obstructions to energy  component commercialization throughout the long term, as  well as the power module's expected significant job in a  future low-carbon green economy.
Keywords: Energy; Environment; Fossil; Fuel; Renewable